2009
DOI: 10.3390/molecules14114725
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Composition and Phytotoxic Effects of Essential Oils of Salvia hierosolymitana Boiss. and Salvia multicaulis Vahl. var. simplicifolia Boiss. Growing Wild in Lebanon

Abstract: The chemical composition of the essential oils of S. hierosolymitana Boiss. and S. multicaulis Vahl. var. simplicifolia Boiss. collected in Lebanon was studied by means of GC and GC-MS analysis. In all 115 compounds were identified: 82 for S hierosolymitana and 72 for S. multicaulis var. simplicifolia. The presence of carbonylic compounds (17%) characterizes the oil from S. hierosolymitana, while S. multicaulis var. simplicifolia oil is rich of monoterpenes (34.5%) and sesquiterpenes (46.9%). The effects of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 50 publications
(28 citation statements)
references
References 37 publications
0
27
1
Order By: Relevance
“…Interestingly, neither of the above species had dose dependent phytotoxic effect on the tested plants, which could be due the fact that the studied oils contained trace amounts of the toxic monoterpenes 1 and 2 (Mancini et al 2009). …”
Section: Allelopathic Interactionmentioning
confidence: 87%
“…Interestingly, neither of the above species had dose dependent phytotoxic effect on the tested plants, which could be due the fact that the studied oils contained trace amounts of the toxic monoterpenes 1 and 2 (Mancini et al 2009). …”
Section: Allelopathic Interactionmentioning
confidence: 87%
“…Indeed, other reports showed that limonene, a-pinene, and ocimenone inhibited the root growth of the Zea mays (Scrivanti et al 2003). Mancini et al (2009) andDe Martino et al (2010a, b) have demonstrated that both apinene and limonene inhibited the germination and radicle elongation of R. sativus and Lepidium sativum. Although the mode of inhibitory action of essential oils against germination still remains unclear, several articles reported that volatile oils and monoterpenoids inhibit cell division and induce structural breaks and decomposition in roots (Singh et al 2006b;De Martino et al 2010a).…”
Section: S Arvensismentioning
confidence: 96%
“…Despite their importance in plant protection and food science, the environmental effects regulating the production of volatile compounds in Salvia plants have seldom been examined. As a continuation of our studies on genus Salvia (Cardile et al, 2009;Mancini et al, 2009;Canzoneri et al, 2011;Tenore et al, 2011), the objective of this study was to understand if essential oil production and yield of an agriculturally important Lamiaceae of the Mediterranean area, S. officinalis L., will be affected by environment. We also describe the biological activity of the essential oils collected in different places against three human melanoma cells (A375, M14, and A2058), testing several biochemical parameters, such as cell vitality, cell membrane integrity, genomic DNA fragmentation and caspase-3 activity.…”
Section: Introductionmentioning
confidence: 99%